Evolution of NACA23012 wake vortices structure using PIV - Elsayed, Omer Ali; Asrar, Waqar; Omar, Ashraf Ali; Kwon, Kijung (American Society of Civil Engineers (ASCE), 2012)
The formation and development of a wing‐tip vortex in a near and extended near field were studied experimentally. A swept‐back tapered wing with a NACA23012 cross‐section was used as a vortex generator. Particle image velocimetry as a whole field velocity measurement technique was used in a low‐speed wind tunnel to measure and characterize the wing tip vortex. Wake structures at successive downstream planes crosswise to the axis of the wake vortices were evaluated in terms of internal and external core radius, maximum tangential velocities, vorticity and circulation distributions. The effect of angle of attack on vortex parameters was examined at one downstream location. Internal core radius and circulation distributions were nearly constant along the downstream direction. A direct dependence of the circulation and tangential velocity distribution on the angle of attack was evident. The centers of the wing tip vortices scatter in a circle of radius nearly equal to 1% of the mean wing chord. Meandering amplitudes showed no direct dependence on the vortex strength but increase along the downstream direction. Good agreement was obtained between the theoretical exponential vortex model and the measured data. Computed induced rolling moment coefficients generated by the wing are within the full roll control capability of a follower aircraft.